Déficit hídrico sobre indicadores de crescimento e fisiológicos de Bidens pilosa L. e Bidens subalternans DC. - Freitas, Márcio Alexandre Moreira de (Universidade Federal Rural do Semi-Árido, 2018)
Stress caused by soil water deficit has been one of the main factors that hinder plant growth. The understanding of the factors related to the behavior of weed species under conditions of water stress can contribute to the elaboration of efficient management strategies. Two experiments were carried out to evaluate the effects of the degree and duration of water stress on physiological and growth indicators of two weed species (Bidens pilosa L. and Bidens subalternans DC). The simulation of the stress degree was performed by evaluating four levels of vessel capacity: 100, 75, 50, 25%. The study of water stress duration included five treatments: 0, 1, 2, 3, 4, 5 and 6 days of irrigation interval. The two experiments were carried out in a randomized block design, with six replications. In both experiments, the photosynthetic rate (A; μmol CO2 m-2), stomatal conductance (gs; μmol H2O m-2 s-1), transpiration (E; mmol H2O m-2 s-1), the number of leaves per plant and the dry matter of roots, stems, leaves and total. The results of the degree and duration of stress experiments show that the species of B. pilosa and B. subalternans can stand conditions of low water availability in the soil. The mechanisms involved for this ability may be related to the reduction of the stomatal opening as well as the loss of leaves by the plant. However, these mechanisms may occur only when soil water availability approaches 25% of the field capacity. The B. subalternans species showed higher sensitivity as the available soil water was reduced, showing a greater reduction in the dry matter of leaf, stem and root, compared to B. pilosa species
Water deficit on growth and physiological indicators of Bidens pilosa L. e Bidens subalternans DC.
Keywords: planta daninha; Estresse abiótico; Picão-preto; Weed; Abiotic stress; Blacksting; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA